2018
DOI: 10.1016/j.jacl.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pemafibrate (K-877), a selective peroxisome proliferator-activated receptor α modulator, in patients with dyslipidemia: Results from a 24-week, randomized, double blind, active-controlled, phase 3 trial

Abstract: Pemafibrate was superior to fenofibrate in terms of serum TG-lowering effect and hepatic and renal safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
143
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(167 citation statements)
references
References 46 publications
20
143
1
3
Order By: Relevance
“…The FIRST study showed that, in the fenofibric acid group during the 104‐week treatment period, 2.7% of participants had a serum creatinine level >2.0 mg/dL and 20.7% and 2.1% of participants had a 1.5‐fold and 2‐fold increase from baseline, respectively, with these percentages being higher than those in the placebo group. Previous studies comparing the effects of pemafibrate with those of fenofibrate showed that pemafibrate had a smaller effect than fenofibrate on serum creatinine levels, which was also confirmed during our long‐term treatment of 52 weeks in people with type 2 diabetes (Table ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The FIRST study showed that, in the fenofibric acid group during the 104‐week treatment period, 2.7% of participants had a serum creatinine level >2.0 mg/dL and 20.7% and 2.1% of participants had a 1.5‐fold and 2‐fold increase from baseline, respectively, with these percentages being higher than those in the placebo group. Previous studies comparing the effects of pemafibrate with those of fenofibrate showed that pemafibrate had a smaller effect than fenofibrate on serum creatinine levels, which was also confirmed during our long‐term treatment of 52 weeks in people with type 2 diabetes (Table ).…”
Section: Discussionsupporting
confidence: 86%
“…Although further investigation is needed to justify the difference in the clinical profile of pemafibrate from that of other fibrates, pemafibrate is reported to have a good benefit–risk balance. Pemafibrate had a TG‐lowering effect equal to or greater than that of fenofibrate, but the rates of AEs in the pemafibrate group were lower than those in the fenofibrate group . Furthermore, pemafibrate, but not fenofibrate, decreased ALT and GGT levels.…”
Section: Discussionmentioning
confidence: 87%
“…In the current investigation, no severe ADRs were recorded for pemafibrate. The drug has also been reported to have a lower incidence of adverse effects than fenofibrate in patients with dyslipidemia . Additional longer studies are needed to clarify the clinical advantage of pemafibrate with UDCA, especially with regard to effect and safety.…”
Section: Discussionmentioning
confidence: 99%
“…The new selective peroxisome proliferator‐activated receptor α modulator (SPPARM‐α), pemafibrate, was very recently approved for the treatment of dyslipidemia . Dyslipidemia is a common feature in PBC.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical study demonstrated minor fluctuations in both serum creatinine and cystatin C over 24 weeks with pemafibrate compared with the significant increase in these values with fenofibrate treatment. Because patients with CKD typically present with confounding diseases such as dyslipidemia, once approved, pemafibrate may be a suitable alternative agent for this population . In another case report, dosing of an aminoglycoside antibiotic cleared by the kidney corrected for eGFR‐creatinine resulted in overestimation of GFR, accumulation of the drug, and, ultimately, AKI in an elderly man.…”
Section: Recommendations For Renal Impairment Studies In Drug Developmentioning
confidence: 99%